DETERMINATION OF SEDIMENT ACCUMULATION PATTERN IN A DOUBLE BOTTOM BALLAST TANK MODEL - Devrim Bülent Danişman; Ceren Bilgin Güney; Fatma Yonsel; Şafak Nur Ertürk Bozkurtoğlu (Brodogradnja, 2018)
Ballast tank sediments may cause several problems in a wide range changing from environmental to economical. Its contribution to biological invasion is an important concern. Thus, the sediment management is included as an integral component of the “The International Convention on the Control and Management of Ships’ Ballast Water and Sediments”. The reduction of the amount of the sediment to be removed is of great importance for management issues. Therefore, the convention underlines that ships should be designed and constructed with a view to minimize the uptake and undesirable entrapment of sediments and facilitate removal of sediments. Design and construction solutions can effectively be developed after determination of the problem areas. In this study, sediment accumulation pattern and problem areas in the ballast tank model of a longitudinally framed double bottom tanker is determined. The problem areas are found to be at the mid-section of the tank closer to the centre girder.